2019
DOI: 10.1101/667998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epithelium intrinsic vitamin A signaling co-ordinates pathogen clearance in the gut via IL-18

Abstract: AbstractIntestinal epithelial cells (IECs) are at the forefront of host-pathogen interactions, coordinating a cascade of immune responses to confer protection against pathogens. Here we show that IEC-intrinsic vitamin A signaling restricts pathogen invasion early in the infection and subsequently activates immune cells to promote pathogen clearance. Mice blocked for retinoic acid receptor (RAR) signaling selectively in IECs (stopΔIEC) showed significantly h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…SFB and 16S bacterial levels were similar in dnRAR FF and dnRAR IEC mice (Figures 2E and 2F). Interestingly, dnRAR IEC mice exhibited significantly higher C. rodentium infection compared with floxed controls (dnRAR FF ) ( Figures 2G and 2H), a similar effect previously described for Salmonella typhimurium infection (Gattu et al, 2019;Iyer et al, 2020). To next decipher whether RA-driven protection requires epithelial RAR activation, control and dnRAR IEC mice were treated with RA and infected with C. rodentium.…”
Section: Iec-intrinsic Rar Activation Enhances Defense Against C Rodsupporting
confidence: 74%
See 2 more Smart Citations
“…SFB and 16S bacterial levels were similar in dnRAR FF and dnRAR IEC mice (Figures 2E and 2F). Interestingly, dnRAR IEC mice exhibited significantly higher C. rodentium infection compared with floxed controls (dnRAR FF ) ( Figures 2G and 2H), a similar effect previously described for Salmonella typhimurium infection (Gattu et al, 2019;Iyer et al, 2020). To next decipher whether RA-driven protection requires epithelial RAR activation, control and dnRAR IEC mice were treated with RA and infected with C. rodentium.…”
Section: Iec-intrinsic Rar Activation Enhances Defense Against C Rodsupporting
confidence: 74%
“…Consistent with this, recent studies have discovered that IEC-intrinsic RAR expression promotes defense by regulating antimicrobial peptide production (Gattu et al, 2019;Jijon et al, 2018). Furthermore, the ability of IECs to sense RA is necessary for defense against Salmonella typhimurium (Gattu et al, 2019;Iyer et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Role of RA in maintaining a robust intestinal epithelium barrier is especially important in regulating host microbe interactions (Gattu et al, 2019;Snyder et al, 2020). Loss of intestinal epithelial cell (IEC) intrinsic RA signaling in mice results in defective goblet cell lineage commitment and reduced epithelial cell shedding upon infection (Iyer et al, 2020;Jijon et al, 2018). However, despite RA's critical role in regulating epithelial barrier, we observed that VA metabolic machinery and RA synthesis are suppressed by commensal bacteria, suggesting that IECs depend on an alternate source of RA (Grizotte-Lake et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…A mechanistic explanation for the protective role of vitamin A derivatives in gut infection was recently brought: in a model of salmonella infection in mice, vitamin A stimulates IL-18 production, which acts both on early stages of infection (by promoting cell shedding, i.e., renewal of epithelial barrier and elimination of contaminated cells) and on later stages through Th1 and Th17 responses of immune cells and IFN-γ production, for pathogen clearance. Not surprisingly, this is a RARmediated transcriptional effect (Iyen et al 2020).…”
Section: Benefits (Human Studies)mentioning
confidence: 96%